Efeito do envelhecimento sobre o comportamento mecânico dos músculos papilares de ratos Wistar. - Cicogna, A. C.; Padovani, C. R.; Nardi, S. C.; Okoshi, M. P. (My University, 1993)
PURPOSE--To evaluate the effects of age on mechanical performance of rat myocardium. METHODS--Left ventricular papillary muscles were isolated from male Wistar rats at 1, 3, 6 and 12 months of age. Muscles were studied isometrically and isotonically, stimulated at 0.2 Hz, perfused with Krebs-Henseleit solution having an external calcium concentration of 2.52 mM, and maintained at 28 degrees C. RESULTS--Peak isometric developed tension was significantly higher in 1 month than 3, 6 and 12 months. Peak rate of isometric tension rise decreased substantially between 1, 3 and 12 months. Time to peak isometric developed tension showed a significant increase of both 3 and 12 months of age. Time to half relaxation increased significantly from 3 to 6 and from 3 to 12 months. Maximum rate of tension decline decreased from 3 to 6 and from 3 to 12 months. No difference in resting tension was noted among any group. Isotonically, peak shortening and time to peak shortening increased from 1 to 3 months of age. Time to half re-lengthening increased from 3 to 6 and from 3 to 12 months of age. No difference in peak shortening velocity, peak relaxation velocity and relative change in muscle length was noted among any groups. CONCLUSION--The maturation affects the mechanical performance of cardiac muscle.
Effects of aging on mechanical performance of Wistar rat papillary muscles
Keywords: aging; animal; heart papillary muscle; male; muscle isometric contraction; muscle isotonic contraction; physiology; rat; rat strain; Aging; Animal; English Abstract; Isometric Contraction; Isotonic Contraction; Male; Papillary Muscles; Rats; Rats, Wistar